Cross-Cultural, Aboriginal Language, Discovery Education for Health Literacy and Informed Consent in a Remote Aboriginal Community in the Northern Territory, Australia - Shield, Jennifer M. (Trop Med Infect Dis, 2018)
Background: Education for health literacy of Australian Aboriginal people living remotely is challenging as their languages and worldviews are quite different from English language and Western worldviews. Becoming health literate depends on receiving comprehensible information in a culturally acceptable manner. Methods: The study objective was to facilitate oral health literacy through community education about scabies and strongyloidiasis, including their transmission and control, preceding an ivermectin mass drug administration (MDA) for these diseases. A discovery education approach where health concepts are connected to cultural knowledge in the local language was used. Aboriginal and non-Aboriginal educators worked collaboratively to produce an in-depth flip-chart of the relevant stories in the local language and to share them with clan elders and 27% of the population. Results: The community health education was well received. Feedback indicated that the stories were being discussed in the community and that the mode of transmission of strongyloidiasis was understood. Two-thirds of the population participated in the MDA. This study documents the principles and practice of a method of making important Western health knowledge comprehensible to Aboriginal people. This method would be applicable wherever language and culture of the people differ from language and culture of health professionals.